(untitled) (CIPEEX, 2025)
SUMMARY: Introduction: Relaxing massage is a natural technique that uses manual movements on the soft tissues of the body, promoting benefits to the nervous, muscular, circulatory and lymphatic systems. Without the use of braces, this practice aims to balance health and prevent possible diseases. Objective: To reinforce the importance of therapeutic effects using relaxing massage. Methodology: This was a narrative-type literature review based on scientific articles indexed in the scientific databases: Google Scholar and SciELO. The following DeCS/MeSH descriptors were used: massagem (OR) massage (AND) Práticas Integrativas e Complementares (AND) Complementary Therapies (OR) PICS. The inclusion criteria were: publications between 2017 and 2023 available in English or Portuguese in the full version that covered the theme. Articles that were not subject to the theme, duplications, publications in other languages and that were not scientific articles were excluded. Results: The research was composed of nine scientific articles. Archaeological evidence has shown that massage was already used by Egyptians, Persians, Greeks, and Romans. To ensure safe care, it is essential to carry out a prior evaluation of the patient and work together with a multidisciplinary team. The procedure must be done by a qualified professional, able to recognize signs of contraindication, such as skin lesions or infectious diseases. Among the techniques of relaxing massage, maneuvers such as pressure by stitches, kneading, friction, percussions, vibrations, pinching, fan movements and keys, etc., stand out. Each of them has specific functions, which can be combined for better therapeutic results. Relaxing massage offers several physical and emotional benefits, such as reduced fatigue, muscle relaxation, improved flexibility and motor coordination, in addition to helping to combat insomnia and anxiety, especially in young people. It also favors circulation, benefiting the skin, pregnancy and labor. Conclusion: Relaxing massage is an effective technique that promotes several physical and emotional benefits, contributing to balance and preventing dysfunctions in the body, and can be applied in various human health conditions. KEYWORDS: Massage. Massage therapy. Reflexology. Complementary Therapies.